Dominance in Confinement: The Complex Roles of Female Slaves in Mughal Harem and Their Ascendancy - Zaman, Rizwana (DIROSAT: Journal of Education, Social Sciences & Humanities, 2026)
The paper deals with the role and status of female slaves in the Mughal period in medieval India, particularly in the imperial harem. The research explores and highlights the dominating and dignified role of the concubines and other female slaves of foreign origin, in the imperial harem in contrast to those of local female slaves having less attractive physical attributes and were assigned household and domestic tasks. It also categorizes the female slaves according to their positions and duties assigned to them, which they were bound to perform. The paper highlights the nature, organization of harem, femininity, social and cultural role of female slaves. It also discusses the methods of enslavement, legalization of slave trade, traditions of imperial harem and the social status of female slaves who were the important and most significant part of the Mughal household. The present research includes primary as well as secondary sources to show the novel portrait of the female slaves during this particular period.